Novel Hybrid CHC from β-carboline and N-Hydroxyacrylamide Overcomes Drug-Resistant Hepatocellular Carcinoma by Promoting Apoptosis, DNA Damage, and Cell Cycle Arrest - Miao, Jiefei; Meng, Chi; Wu, Hongmei; Shan, Wenpei; Wang, Haoran; Ling, Changchun; Zhang, Jinlin; Yang, Tao (Frontiers in Pharmacology, 2021)
A novel hybrid CHC was designed and synthesized by conjugating β-carboline with an important active fragment N-hydroxyacrylamide of histone deacetylase (HDAC) inhibitor by an amide linkage to enhance antitumor efficacy/potency or even block drug resistance. CHC displayed high antiproliferative effects against drug-sensitive SUMM-7721, Bel7402, Huh7, and HCT116 cells and drug-resistant Bel7402/5FU cells with IC50 values ranging from 1.84 μM to 3.27 μM, which were two- to four-fold lower than those of FDA-approved HDAC inhibitor SAHA. However, CHC had relatively weak effect on non-tumor hepatic LO2 cells. Furthermore, CHC exhibited selective HDAC1/6 inhibitory effects and simultaneously augmented the acetylated histone H3/H4 and α-tubulin, which may make a great contribution to their antiproliferative effects. In addition, CHC also electrostatically interacted with CT-DNA, exerted remarkable cellular apoptosis by regulating the expression of apoptosis-related proteins and DNA damage proteins in Bel7402/5FU cells, and significantly accumulated cancer cells at the G2/M phase of the cell cycle by suppressing CDK1 and cyclin B protein with greater potency than SAHA-treated groups. Finally, CHC displayed strong inhibitory potency to drug-resistant hepatic tumors in mice. Our designed and synthetic hybrid CHC could be further developed as a significant and selective anticancer agent to potentially treat drug-resistant hepatocellular carcinoma.